Image Processing of Sentinel-1A Data for Ground Displacement Monitoring and Landslide Hazard Assessment in Rinjani Area - Ramdani Saputra; Heri Sulistiyono; Teti Zubaidah (Journal of Renewable Energy, Electrical, and Computer Engineering, 2026)
Landslides are a persistent geological hazard, especially in seismically active and high-rainfall regions such us Lombok Island, Indonesia. This study addresses landslide susceptibility in Sembalun Bumbung Village, located within the Rinjani Area, by integrating ground displacement monitoring with multi-parameter spatial analysis. Advanced image processing techniques were applied to Sentinel-1A Interferometric Synthetic Aperture Radar (InSAR) data, specifically processed using Differential Interferometric Synthetic Aperture Radar (DInSAR) technique, to observe and quantify annual ground displacement from 2019 to 2024. Simultaneously, a landslide susceptibility map was developed through the analysis of five key environmental parameters: rainfall, rock type, slope gradient, land cover, and soil type; each weighted and scored based on their empirical contributions to landslide risk. The DInSAR analysis revealed annual ground displacement values ranging from 0.030 to 0.105 meters, with the highest rates detected at points T6 and T7 in Benyer Hamlet. The resulting landslide susceptibility map categorized areas into five susceptibility levels (very low, low, moderate, high, and very high). Notably, points exhibiting a very high susceptibility (e.g., T1 in Bebante Daya Hamlet, T2 in Jorong Utara Hamlet, as well as T6 and T7 in Benyer Hamlet) consistently correlated with the highest annual displacement values observed from the DInSAR analysis. This integrated approach offers a solid basis for targeted mitigation strategies, including enhanced monitoring, risk communication, land-use planning, and potential early warning systems.